Design of Novel Tricaprylin-Incorporated Multi-Layered Liposomal System for Skin Delivery of Ascorbic Acid with Improved Chemical Stability - Myoung Jin Ho; Dong Woo Park; Myung Joo Kang (MDPI AG, 2023)
L-ascorbic acid (Vit C) possesses a variety of dermatological functions in maintaining skin health and anti-aging properties. However, its topical application is challenging owing to its liability to light, oxygen, or heat. Therefore, in this study, a novel liposomal system, including a lipophilic neutral oil named a lipo-oil-some (LOS), was designed to improve the chemical stability and aid the skin absorption of Vit C. The vesicular systems were prepared using the ethanol injection method, employing phosphatidylcholine, cholesterol, dipalmitoyl-sn-glycerol-3-phosphoglycerol, and tricaprylin as neutral oil. The optimized LOS was characterized as follows: shape, multi-layered sphere; size, 981 nm; zeta potential, −58 mV; and Vit C encapsulation efficiency, 35%. The encapsulation of the labile compound into the novel system markedly enhanced photostability, providing over 10% higher Vit C remaining compared to Vit C solution or Vit C-loaded conventional liposome under a light intensity of 20,000 lx. On the other hand, the ex vivo skin permeation and accumulation of Vit C with the LOS system were comparable to those of smaller conventional liposomes (198 nm) in a Franz diffusion cell model mounted with porcine skin. Based on these findings, we concluded that the novel liposomal system could be utilized for skin delivery of Vit C with enhanced chemical stability.